Pengaruh Beban Kerja, Coping Stress, dan Motivasi Terhadap Produktivitas Kinerja Guru - Mayasari, Mayasari; Nainggolan, Ika Frida Varinsi; Admannur, Febby; Sitanggang, Ricky Affandy; Simanjuntak, Usrianto; Lubis, Hasrita; Safrida, Safrida (Journal of Management and Economics Research, 2024)
This research was conducted with the aim of determining the influence of workload, stress coping and motivation on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. The research was conducted using a quantitative approach, while the research respondents were 67 teachers at SMP Negeri 1 Idi, East Aceh Regency. The conclusions of the research conducted include: 1) There is a positive and significant influence between workload on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount < ttable, namely 3.126 > 1.668 with a significance of 0.002 < 0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 2) There is a positive but not significant influence between stress coping on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount > ttable, namely 0.050 < 1.668 with a significance of 0.960 > 0.05. This means that the research hypothesis H0 is accepted and H2 is rejected. 3) There is a positive and significant influence between motivation and teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount < ttable, namely 6.982 > 1.669 with a significance of 0.000 < 0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 4) There is a positive influence between workload, stress coping and motivation on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is based on the results of research conducted using the F test (simultaneous test) that the variables consisting of workload (X1), coping stress (X2), motivation (X3) have a significant value of α 0.000 < 0.05 and the value of Fcount > Ftable ( 136,452 > 3.13). Thus, the decision is obtained that H0 is rejected and H4 is accepted. The coefficient of determination (R Square) is R Square 0.860 or equal to 86%. This figure means that the variables Workload (X1), Coping Stress (X2), Motivation (X3) simultaneously (together) influence the Teacher Productivity variable (Y) by 86%. While the remainder is 100% - 86% = 14%. This means that 14% is influenced by other variables outside the regression equation or the variables studied.